Different Uses of the Conjunction Fa In The Arabic Language - Kocabıyık, Halil İbrahim; Açar, Yeliz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The letter fā is widely used in Arabic after the letter wāw and has many meanings. This letter has no exact equivalent in Turkish. It gains meaning according to the position in which it is used. Knowing the meanings of this letter, in general, will contribute to the correct understanding of sentences and texts. The letter fā can be called both a preposition and a conjunction since it is one of the ḥurūf al-maʿānī (meaning letters) and establishes a connection between words and sentences. This study mentions the places where the letter fā is used as a conjunction, such as linking words and sentences together as the letter of attribution, expressing causation, and linking conditional and punitive sentences together. In addition, the cases where this letter comes as zā’id /supplemental/extra and other uses of this letter are also included. When the letter fā is used in the ʿaṭf/attributive function, it expresses a familiar role between “maʻṭūf” and “maʻṭūf ʿalayh”, “tartīb/arrangement” and “taʿqīb/succession”. The letter fā can also indicate cause in addition to tartīb and taʿqīb. In this case, the part before fā becomes the cause of the part after it. In addition, in some cases, this letter can express mere cause without the function of attribution. These cases are as follows: When the letter fā comes after an imperative verb, a prohibition (النهي), a question (الاستفهام), a negation (النفي), a request (العرض), an encourage (التحضيض), a wish expression (التمني), and a hope (الترجِّي).